The role of the physical education and sports class in reducing school violence for the adolescent student- A field study at Saleh Muhanna High School - Karkara - Skikda - Bouattit, Djalaleddine (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2023)
Currently, physical and sports education is considered one of the most important fields that contribute effectively to handling with various health, psychological, and social problems facing individuals and groups, especially in the educational field. The physical and sports education class is a good place and time for students to receive a set of theoretical and practical skills that help them build their personality as well as maintain their mental and physical health in order to devote the spirit Community, good interaction with others, and avoiding all forms of violence inside the school. This study aimed to highlight the role of the physical education and sports class in reducing school violence among the adolescent student. The descriptive approach was used by applying a questionnaire to a sample of 80 male and female students at the secondary level of Saleh bin Muhanna - Karkara – Skikda. The results concluded that the physical and sports education class has a role in reducing physical, verbal, and symbolic violence among the adolescent student in the research institution